When are preferences consistent? The effects of task familiarity and contextual cues on revealed and stated preferences - Felix Schläpfer; Baruch Fischhoff (University of Zurich, Socioeconomic Institute, 2010)
Traditionally, economists make a sharp distinction between stated and revealed preferences, viewing the latter as more fully meeting the assumptions of economic analysis. Here, we consider one form of empirical evidence regarding this belief: the consistency of choices in stated and revealed preference tasks. We show that both kinds of task can produce consistent choices, suggesting that both can measure underlying preferences, if necessary conditions are met. We propose that a necessary condition is that task be either familiar to those facing it or offer contextual cues that substitute for familiarity, such as prices in competitive markets or recommendations from trusted, knowledgeable sources. We show that how well decision makers achieve such understanding is often confounded with the method that researchers use. Considering task familiarity not only clarifies some of the conflicting evidence regarding revealed and stated preference methods, but raises potentially productive questions regarding the roles of social institutions in shaping preferences.
Keywords: D01; D03; Q51; 330; consistency; contingent valuation; framing; public goods; revealed preferences; stated preferences; validity.; Offenbarte Präferenzen; Willingness to pay; Öffentliche Güter; Theorie